2019
DOI: 10.1038/s41598-019-41708-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on the inflammatory response during robot-assisted laparoscopic radical prostatectomy: a prospective randomized controlled study

Abstract: Robot-assisted laparoscopic radical prostatectomy (RALRP) is a minimally invasive procedure; however, some amount of surgical trauma that can trigger systemic inflammation remains. Moreover, pneumoperitoneum during RALRP induces ischemia–reperfusion injury (IRI). Propofol, an anesthetic, is known to have anti-inflammatory and antioxidant properties. In the present study, we compared the effects of propofol with those of desflurane on inflammation and IRI during RALRP via measurements of different biomarkers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…We used propofol as an anesthetic agent. It has been reported that intraoperative serum IL-6 levels were lower in general anesthesia compared with desflurane [ 15 ]. Moreover, it suppressed the release of inflammatory cytokines by lipopolysaccharides [ 16 ]; hence, propofol was selected in this case.…”
Section: Discussionmentioning
confidence: 99%
“…We used propofol as an anesthetic agent. It has been reported that intraoperative serum IL-6 levels were lower in general anesthesia compared with desflurane [ 15 ]. Moreover, it suppressed the release of inflammatory cytokines by lipopolysaccharides [ 16 ]; hence, propofol was selected in this case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that remifentanil can suppress the cellular immune response in sepsis and may be protective for lungs, which are one of the earliest affected organs [ 31 ]. Some researchers found that opioid analgesics may significantly reduce cytokine response, and propofol and remifentanil suppress TNF-α and IL-6 induction, thus affecting neutrophil migration and adhesion molecule expression [ 19 , 32 ] Recently, studies on the protective effects of remifentanil against intestinal, hepatic and myocardial I/R injury have been reported [ 33 , 34 ]. These studies show that remifentanil prevents I/R damage in the local target organ.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its structural characteristics, it has free radical scavenging properties. As propofol is highly lipid-soluble, it particularly accumulates on lipophilic membranes, which are very sensitive to oxidative injury, and may increase or prevent the decrease in antioxidant capacity [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fifthly, a cost analysis with the use of the three agents was not a part of the present study. Finally, more outcomes, including the incidence of intraoperative awareness and body movement, and mechanism parameters, such as alterations in the stress response (catecholamines, noradrenaline, adrenaline, adrenocorticotropic hormone and cortisol) or inflammation factors (interleukin-6, tumor necrosis factor-α, C-reactive protein and nitric oxide) (33,34) should be recorded to comprehensively assess the anesthetizing effects of lower-dose desflurane combined with PR. The present study suggested that combining low-dose desflurane with PR may represent an efficient anesthesia regimen to prevent the hemodynamic instability of total intravenous anesthesia for patients undergoing laparoscopic gynecological surgery.…”
Section: Discussionmentioning
confidence: 99%